Correlation of Peripapillary Retinal Nerve Fibre Layer Thickness and Visual Evoked Potential in Optic Neuritis in a Tertiary Eye Care Centre - Godar, Manita Sunam; Sharma, Ananda Kumar; Thapa, Madhu; Sitaula, Sanjeeta; Gamal, Nita Sunam; Manandhar, Laxmi Devi (Nepalese Journal of Ophthalmology, 2019)
Introduction: Optic neuritis (ON) is the involvement of the optic nerve as a result of inflammation, demyelination or infection.Objective: To study the correlation between peripapillary retinal nerve fibre layer thickness (pRNFL) and visual evoked potential (VEP) in ON cases.Materials and Method: A non-interventional, descriptive, cross sectional study enrolling 66 eyes of 49 patients with ON was done. pRNFL thickness was measured by Optical Coherence Tomography (OCT) and VEP was also done. OCT and VEP findings were compared with the control group. In addition correlation between pRNFL thickness and VEP was done.Results: The mean pRNFL in affected eyes were significantly higher than the control superiorly (p-value